Oral Squamous Cell Carcinoma: Features and Medico-Legal Implications of Diagnostic Omission - Davide Albano; Antonina Argo; Giuseppa Bilello; Enzo Cumbo; Melania Lupatelli; Pietro Messina; Fabio Massimo Sciarra; Mario Sessa; Stefania Zerbo; Giuseppe Alessandro Scardina (Case Reports in Dentistry)
Early diagnosis of oncologic pathologies has a crucial role to determine patient’s prognosis and therapeutic path. Nonetheless, clinical errors and omissions that can occur during diagnostic, as well as detection of preneoplastic or neoplastic condition, may result in devasting consequences both for patients in terms of health and for professionals in terms of medico-legal responsibility. This study is aimed at examining in depth, through the presentation of a specific clinical case, the medico-legal aspects inherent to the diagnosis of oral cancer, analyzing the preventive, interceptive, and diagnostic strategies, the legal implications of clinical evaluation errors and diagnostic omission, and the type of medical damage produced and professional liability. The medico-legal landscape surrounding oral squamous cell carcinoma is multifaceted and characterized by diagnostic challenges, treatment complexities, and legal considerations. Health-care providers must remain vigilant in navigating these complexities to ensure optimal patient care while mitigating legal risks. By prioritizing high-quality medical records, fostering transparent communication with patients, and implementing preventive strategies, health-care institutions can strive to minimize the incidence of litigation and uphold standards of ethical practice in oral carcinoma cases. Additionally, continued research and education in forensic and legal medicine are essential in informing evidence-based practices and promoting patient safety in this evolving field.